2023
DOI: 10.1017/s1092852923001177
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in adults with borderline personality disorder

Abstract: Objective Borderline personality disorder (BPD) is a common and disabling mental health disorder and has detrimental effects on affected individuals across multiple domains. We aimed to investigate whether individuals with BPD differ from control subjects in terms of cognitive functions, and to see if there is a relationship between cognitive functions, impulsivity, and BPD symptom severity. Methods BPD individuals (n = 26; mean age = 26.7; 69.2% female) and controls (n = 58; mean age = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The study interestingly reported a significant positive association between borderline personality disorder symptom severity and impulsivity. Also, the cognitive flexibility of patients with borderline personality disorder is significantly compromised than the healthy controls; however, no association between borderline symptom severity and cognitive functions was measured 1 …”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The study interestingly reported a significant positive association between borderline personality disorder symptom severity and impulsivity. Also, the cognitive flexibility of patients with borderline personality disorder is significantly compromised than the healthy controls; however, no association between borderline symptom severity and cognitive functions was measured 1 …”
mentioning
confidence: 87%
“…The study of Aslan et al 1 has not ruled out psychiatric comorbidities like other personality disorders, depression, and anxiety disorders in their study, which can be a major confounder in this study. Though the authors have acknowledged their limitations, it is known that these psychiatric conditions can significantly affect cognition and impulsivity as well as can mask the symptom severity of borderline personality disorder.…”
mentioning
confidence: 91%
See 2 more Smart Citations